2015
DOI: 10.1021/acs.macromol.5b00137
|View full text |Cite
|
Sign up to set email alerts
|

POSS-Containing Jacketed Polymer: Hybrid Inclusion Complex with Hierarchically Ordered Structures at Sub-10 nm and Angstrom Length Scales

Abstract: A series of organic−inorganic hybrid polymers, PnPOSS (n = 6, 10, which is the number of carbon atoms in the flexible alkyl spacers), containing a mesogen-jacketed liquid crystalline polymer (MJLCP) as the main chain and a crystalline nanobuilding block, polyhedral oligomeric silsesquioxane (POSS), in the side chains were designed and synthesized for constructing a hybrid inclusion complex. The phase structures and phase transitions of PnPOSS were investigated by differential scanning calorimetry, polarized li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…These peaks correspond to the rhombohedral packing of the POSS moieties. 35,36 The PEO-rich microphase remains amorphous at these temperatures ( Figure S11a Figure 2) and TEM (Figure 4). The effect of crystallinity on ordered microphases in block copolymers is a subject of long-standing interest.…”
Section: Rheologymentioning
confidence: 90%
“…These peaks correspond to the rhombohedral packing of the POSS moieties. 35,36 The PEO-rich microphase remains amorphous at these temperatures ( Figure S11a Figure 2) and TEM (Figure 4). The effect of crystallinity on ordered microphases in block copolymers is a subject of long-standing interest.…”
Section: Rheologymentioning
confidence: 90%
“…The casting solution containing PS4VP was prepared with the same method as demonstrated before . Before it was brought into contact with the PS4VP dope solution, the PVDF hollow‐fiber membrane was immersed in the intermediate‐treatment agent 1,4‐dioxane for 5 s to control the extent of the casting solution interpenetration into the porous support layer .…”
Section: Methodsmentioning
confidence: 99%
“…[41b] Zhu et al reported as eries of POSS-embedded LC polymers comprising am esogen-jacketedl iquid crystallinep olymer as the main chain and POSS attached as the side chain. [42] Based on 1D and 2D wide-angle X-ray diffractiona nd temperaturedependents ynchrotron-radiation small-angle X-ray scattering experiments, P5 with n = 10 acted as as upramolecular rod-like mesogen and exhibited a2 Dh exagonal columnar (Col h )p hase. In the columnar assembly,t he polystyrene polymerb ackbone was envisaged to stay in the center with the POSS pendants staggered around the periphery,p resumably formingahelixlike structure.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Zhu et al reported a series of POSS‐embedded LC polymers comprising a mesogen‐jacketed liquid crystalline polymer as the main chain and POSS attached as the side chain . Based on 1D and 2D wide‐angle X‐ray diffraction and temperature‐dependent synchrotron‐radiation small‐angle X‐ray scattering experiments, P5 with n =10 acted as a supramolecular rod‐like mesogen and exhibited a 2D hexagonal columnar (Col h ) phase.…”
Section: Application Of Poss As Functional Materialsmentioning
confidence: 99%